TRANSCRANIAL MAGNETIC STIMULATION OF THE CEREBELLUM - Minks, Eduard; Kopickova, Marie; Marecek, Radek; Streitova, Hana; Bares, Martin (Biomedical papers, 2010)
Introduction: The cerebellum is a very complex structure with many motor/non-motor functions and direct and indirect connections with almost the entire central nervous system. Transcranial magnetic stimulation (TMS) is a non-invasive electrophysiological method for studying, diagnosing, and treating disorders of the nervous system. The aim of the present review is to summarise the research and potential clinical uses of cerebellar TMS.Methods: PubMed literature search using the key words ``cerebellum TMS''.Results: TMS of the cerebellum is used in two types of protocols. The first type involves the separate stimulation of the cerebellum while tracking its clinical or electrophysiological influence on motor and non-motor functions. The second involves stimulation of the cerebellum as a conditioning stimulus before stimulating the motor cortex, to monitor the electrophysiological impact of cerebellar stimulation on the motor cortex. Most studies are performed on small groups of healthy volunteers; isolated studies are performed on patients with neurological disorders (spinocerebellar ataxia, migraine, dystonia, Miller Fisher syndrome). It has been shown that cerebellar TMS is able to influence motor systems, memory, and perception of time, and there is evidence of its electrophysiological effects in the frontal cortex.Conclusion: Published studies suggest that cerebellar TMS is currently only important in research. There is not yet any clear or reliable evidence of the therapeutic effects of cerebellar TMS. However, its use as a treatment method can be anticipated.
Keywords: TMS/rTMS/Transcranial magnetic stimulation/Cerebellum/Intracortical facilitation/Intracortical inhibition